Eosinophilic Pneumonias - Akuthota, Praveen (American Society for Microbiology, 2012)
Summary: This review starts with discussions of several infectious causes of eosinophilic pneumonia, which are almost exclusively parasitic in nature. Pulmonary infections due specifically to Ascaris, hookworms, Strongyloides, Paragonimus, filariasis, and Toxocara are considered in detail. The discussion then moves to noninfectious causes of eosinophilic pulmonary infiltration, including allergic sensitization to Aspergillus, acute and chronic eosinophilic pneumonias, Churg-Strauss syndrome, hypereosinophilic syndromes, and pulmonary eosinophilia due to exposure to specific medications or toxins.